Incidence of Pituitary Incidentalomas in Patients with Adrenal Adenomas - Chrisoulidou, A.; Alexandraki, K. I.; Kita, M.; Tsolakidou, K.; Papanastasiou, L.; Samara, C.; Anastasiou, A.; Piaditis, G.; Kaltsas, G. (Experimental and Clinical Endocrinology & Diabetes, 2014)
With the advent of modern imaging modalities, endocrine incidentalomas are increasingly being discovered. We aimed to investigate the presence of pituitary incidentalomas (PI) in patients with adrenal incidentalomas (AI), and identify potential metabolic correlates in this cohort. 26 patients (18 females) with AI discovered on abdominal computerized tomography were studied. All patients underwent pituitary magnetic resonance imaging (MRI) and endocrine investigations to evaluate functional adrenal pathology, anterior pituitary hormonal status, insulin-resistance indices and presence of metabolic syndrome. Pituitary MRI revealed a microadenoma and a 4×5 mm cyst in 1 patient respectively, and an empty sella in 4 (2 partial) patients. Overall, 6/26 (23%) patients with an AI had evidence of pituitary imaging pathology but only 8% had a PI; none had any evidence of abnormalities in pituitary function. Subclinical hypercortisolism was the only hyperfunctional status detected in 4 patients with AI but was unrelated to the pituitary findings. No abnormality of insulin secretion and action was found between patients with or without pituitary pathology. In the present study 23% of patients with AI had some alteration in pituitary morphology, and 2 a PI without accompanying pituitary hormonal deficit or metabolic derangement. Further studies are required to address this issue and identify a potential pathogenetic mechanism.
Keywords: pituitary incidentalomas; adrenal incidentalomas; insulin resistance; beta-cell function